Digital Marketing Training and Assistance for SMEs as an Effort to Improve the Jabet Sop Sales Service - Sri Wahyuni; Welda Mudiar; Andyni Yulfanis Aulia Masrifa (Institute for Research and Community Services, 2019)
From their developments, food stalls, especially those in DKI Jakarta, experienced very rapid growth. The increasing number of businesses in the culinary field provides the consumers with many choices. For soup fans in Jakarta, one alternative is Jabet Sop. In one area in Kemayoran Subdistrict, Serdang District, there are several SMEs and one of them is Jabet Sop. Perbanas IKPIA, in collaboration with the DKI Jakarta Department of Industry and Energy, provided training for SMEs in making financial reports and simple bookkeeping and building adequate business facilities and infrastructure. This method of community-empowerment activities was carried out through training and mentoring programs and resolving ongoing problems by providing entrepreneurial motivation and managerial skills training, training in the use of information technology for marketing. After the training, Jabet Sop has been able to market their product through social media namely IG, become a merchant of both GrabFood and GoFood, provide decent facilities and infrastructure such as tables, and prepare financial statements and bookkeeping.